2009
DOI: 10.1159/000213495
|View full text |Cite
|
Sign up to set email alerts
|

Current Situation of Endotoxin Retentive Filter

Abstract: Most Japanese facilities use central dialysis fluid delivery systems (CDDS). In addition, since high-performance dialysis membranes are frequently used in Japan, the standard recommends that ultrapure dialysis fluid (UPD) should be used for all dialysis modalities at all dialysis facilities. RO produces and endotoxin retentive filters (ETRFs) occupy the most important position for UPD in this CDDS process. But ETRF is not accepted as medical equipment now in Japan. Since the logarithm reduction value (LRV) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The endotoxin cutting filter is a highly efficient tool to maintain the dialysate solution flowing into the dialyzer clean and avoid the introduction of bacteria and endotoxins in the hemodialysis patient. 12,13 Our results also indicated the efficiency of the endotoxin cutting filter (Table 1). However, the filters are not changed regularly; moreover, they can break down anytime, and this can remain undetected.…”
Section: Discussionsupporting
confidence: 66%
“…The endotoxin cutting filter is a highly efficient tool to maintain the dialysate solution flowing into the dialyzer clean and avoid the introduction of bacteria and endotoxins in the hemodialysis patient. 12,13 Our results also indicated the efficiency of the endotoxin cutting filter (Table 1). However, the filters are not changed regularly; moreover, they can break down anytime, and this can remain undetected.…”
Section: Discussionsupporting
confidence: 66%
“…One method to produce and ensure the production of ultrapure dialysis fluid is to place an ultrafilter in the hydraulic path between the patient and the dialysis machine, as this filter will have the greatest impact to the final dialysis fluid solution prior to entrance into the dialyzer (Oliver et al, 1992;. Studies in the literature have revealed significant removal rates for ultrafilters in vitro, typically >99% for endotoxin (Oliver et al, 1992;Krautzig et al, 1996), with log reduction values >3 desirable (Tsuchida et al, 2009). Ultrafilters are commonly used in HDF, where two filters are typically used in series to guarantee sterile fluid production -manufacturers of ultrafilters state that sterility of substitution fluid is only guaranteed if the machine feed water falls within certain criteria (Penne et al, 2009).…”
Section: Discussionmentioning
confidence: 99%